THE EFFECT OF FRACTION PUZZLE MEDIA ON THE PROBLEM SOLVING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Putra Kaya Harahap, M. Abrar; Rora Rizky Wandini (Auladuna: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to see how fraction puzzle media influences students' ability to solve problems, assess the effectiveness of puzzle media, and students' responses to media use. This study uses a quantitative method with a pre-experimental type one group pretest-posttest design approach. A total of 31 students from Wira Mandiri Private Elementary School in Medan Labuhan District, Medan City, were used as samples in this study. This study uses several instruments, including tests, student, and teacher response questionnaires. Through the research that has been conducted, it was found that fraction puzzle media has a positive influence on problem-solving abilities. The average student score increased during the post-test after the media was used compared to the pre-test. Positive responses can be seen from the teacher and student response questionnaires, this media is considered effective and suitable for use during the learning process. The findings in this study provide an overview that using fraction puzzle media can facilitate understanding of fraction concepts while strengthening students' ability to solve problems.